PERBEDAAN TINGKAT PENGETAHUAN PASIEN SEBELUM DAN SESUDAH PEMBERIAN LEAFLET TENTANG CARA PENGGUNAAN DAN PENYIMPANAN OBAT TETES MATA DI APOTEK PERINTIS KURIPAN BANJARMASIN - Noverda Ayuchecaria; Sahena Nurzaqia; Nur Fitriani Ahdy (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
The use of eye drops must be as directed in order to obtain an optimal clinical outcome. The storage of eye drops should also receive special attention to ensure sterility. The purpose of this study was to determine differences in the level of patient knowledge before and after giving leaflets. This is an experimental research one group pre test-post test design. Data were collected prospectively. The research was conducted at the Kuripan Perintis Pharmacy, Banjarmasin. The sample in this study amounted to 50 respondents. Data were collected using a questionnaire. The research sample received intervention giving leaflets about the use and storage of eye drops. The research data were displayed in percentage form and analyzed using different test. The results showed that the level of knowledge of respondents about how to use and store eye drops before giving leaflets was in good category 15 (30%); enough 21 (42%) and less (28%). While the level of knowledge of respondents after being given leaflets was in the good category 30 (60%); enough 13 (26%) and less 7 (14%). There was a significant difference between the level of knowledge of the respondents before and after being given the leaflet (p <0.05).